Impact economic of climate change on crop of organic quinua in the Altiplano Region: a Richardian approach - Benique Olivera, Eusebio (2021)
The climate crisis is affecting the production yield of rice, wheat, corn, coffee, beans and other food crops in the country and internationally. The objective of the research was to quantify the impact of climate change on the net income of organic quinoa producers under dry farming conditions in the Altiplano region. Using the Ricardian approach, the impact of climatic variables (temperature and precipitation) on the yield of organic quinoa was estimated in the districts of Cabana, Capachica and Ilave in the Altiplano region, and with primary data collected through a survey to A sample of 237 farmers estimated the value of land productivity. The climatic variables were provided by the National Service of Meteorology and Hydrology of Puno. The results reveal an average production of 1,497 kilos per hectare, obtaining a net income of 14,969 soles per hectare, for a market price of 9.60 soles per kilo. The adaptability of the quinoa producer to climate change was relevant to improve the productivity of the crop. In conclusion, the impact of the agroclimatic variables on the productivity-economic income of organic quinoa producers was marginal in the 2015-2016 agricultural season in the Puno Region.